The easiest way is to use (& to memorize) the sum formula for a AP:
Sum = 1st term added to the last term & multiplied by half the number of terms
S = (a+l)n/2
S = (5 + 53)(7/2) = 203
3x - 1 = 3x + 1
subtract 3x from both sides to get (-1 = 1). This is a false statement so it is: CONTRADICTION
************************************************
4x - 11 = 7
add 11 to both sides and then divide both sides by 4 to get
. This statement is true only when x =
so it is: CONDITIONAL
*************************************************
2 - 8x = 2 - 8x
add 8x to both sides to get (2 = 2). This is a true statement so it is: IDENTITY
*************************************************
x + 1 = -x + 4
add x to both sides, subtract 1 from both sides, and divide both sides by 2 to get
. This statement is true only when x =
so it is: CONDITIONAL
Answer: B, A, C, A
The answer is C the third one to be specific
The way the angles are labeled tell you that they are all congruent. The two triangles you see here also share the side that joins them. Then by the angle-side-angle postulate, the two triangles are congruent, so x + 23 = 13, or x = -10.
It states your "X" will be zero when solving for "Y".
So when solving for "Y" your equation would be;
0+y=4
Then you solve. Y=4
Then you do the same with the "X":
X+0=4. Then you solve. X=4
It would end up being (4(x),4(y) )
Then do the same for the next problem.